Wokół dydaktyki językoznawczej diachronii = On teaching linguistic diachrony - Uździcka, Marzanna; Zarębski, Rafał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This text was written in connection with the participation of the authors in two research projects under the "National Programme for the Development of Humanities" in the years 2011-2014: no 0063/FNiTP/H11/80/2011 - "The history of Polish language and Polish speech communities in 50 Lectures" conducted in the Department of Polish Language History and Pragmatics under the guidance of Professor Stanisław Borawski and no 0089/FNiTP/ H11/08/2011, "Texts for the history of the use of the national language with the annexes" conducted in the Department of Polish Language History at Lodz University under the guidance of Professor Marek Cybulski.
Keywords: dydaktyka akademicka; synteza historycznojęzykowa; wybór; antologia; idea poznawcza; diachronia; academic teaching; historically-linguistics synthesis; anthology; cognitive idea; diachrony